Syrian Industry And Its Contribution To Economic Development - محمود , يوسف; الليوا, ماهر; فارس, ديمة (Latakia University Journal - Economic and Legal Sciences Series, 2021)
This research aims to define the reality of the Syrian industrial sector and analyze its contribution to the national economy, as the industry, with its various sections, is considered one of the basic economic pillars that contribute to bringing about qualitative changes in the process of economic and social development. Jobs chances . The Syrian industries sector, with its various divisions, is one of the important sectors that contribute to achieving a great deal of development depending on strengthening the concept of economic independence for the state by dispensing with imports in addition to providing goods to the population. By studying the contribution of the Syrian industrial sector to the formation of the gross domestic product And the contribution of the Syrian industrial sector in the formation of the gross domestic product. The contribution of the industrial sector in the employment of the labor force. The contribution of the industrial sector to exports. Consequently, reaching a set of results that show the reality of the industrial sector and its contribution to the national economy, in addition to submitting a set of proposals that may contribute to overcoming the causes leading to its low performance in a manner that enables it to achieve the desired goals.